PENGUKURAN DAN PERENCANAAN PERBAIKAN KUALITAS PELAYANAN JASA RENTAL DALAM UPAYA MENINGKATKAN KEPUASAN KONSUMEN - Aulawi, Hilmi; Firmansyah, Ara (Jurnal Mitra Teknik Industri, 2024)
The availability of a comprehensive and varied range of rental equipment constitutes a strength for the company, however, aspects of customer satisfaction may be influenced by certain factors that have not been implemented optimally. Additionally, rental service companies in Garut have yet to conduct a study on the measurement of the level of service quality provided. The purpose of this research is to measure the level of service quality, map the current service positions provided by the service provider, and determine priority quality attributes to formulate improvement plans to enhance customer satisfaction. The approach used is quantitative descriptive, utilizing service quality dimensions proposed by Grönroos as a reference for organizing quality attributes. The research method consists of three stages: first, the Servqual method is used to determine the gap between expected and perceived services; the ZoT method is employed to map quality attributes, providing an overview of the measured quality attribute positions within tolerance limits; and the AHP method is utilized to prioritize attributes for recommended improvements. The research findings indicate overall satisfaction with the measured service quality. However, four quality attributes have negative gaps and fall outside tolerance limits, indicating suboptimal service. Meanwhile, the largest-weighted quality attributes are prioritized in formulating improvement plans, with the “penyedia jasa cekatan (Tangkas) dalam memberikan solusi ketika terjadi yang tidak diharapkan” (C4.3) being the top priority. The analysis of prioritized quality attributes results in the development of a guide or procedure to facilitate the company in addressing customer complaints.